Decoding the therapeutic potential mechanism of Cornus officinalis in Parkinson’s disease: a network pharmacology insight - Wu, Zheng; Zhao, Jiwei; Wang, Wen; Dong, Yuan; Zhou, Taotao; Feng, Yide; Deng, Yalan; Feng, Yingmei (Frontiers in Pharmacology, 2025)
BackgroundCornus officinalis, traditionally used for its kidney-tonifying and waist-protecting properties, has recently shown potential therapeutic effects in neurological disorders. However, its mechanisms in Parkinson’s disease (PD) remain unclear.MethodsThis study employed a network pharmacology approach combined with molecular docking to systematically explore the active components of Cornus officinalis and their associated signaling pathways in PD.ResultsA total of 11,663 PD-related targets were identified from multiple databases, with 185 overlapping targets obtained from active components of Cornus officinalis using SwissTargetPrediction. Protein-protein interaction (PPI) network analysis identified EGFR, TP53, HIF1A, ESR1, PPARG, TNF, HSP90AA1, PTGS2, and SRC as the core targets of Cornus officinalis in PD. Gene Ontology (GO) enrichment analysis revealed that Cornus officinalis primarily modulates pathways such as MAPK signaling, synaptic function, and lipid metabolism. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis highlighted the involvement of target genes in the neuro-endocrine-immune network. Molecular docking confirmed strong binding affinities between active components and core targets, with binding energies below −5 kcal/mol. Reactome pathway enrichment analysis further identified the IL-4 and IL-13 signaling pathway as the most significant, suggesting a critical role in regulating immune responses and neuroinflammation. Molecular dynamics simulations further confirmed the stability of the binding between Cornus officinalis and the targets.ConclusionCornus officinalis exhibits potential therapeutic effects against PD through multi-target and multi-pathway mechanisms, including anti-inflammatory actions, regulation of synaptic function regulation, and metabolic modulation. These findings provide a theoretical foundation for further experimental and clinical validation of Cornus officinalis as a promising candidate for PD treatment.